Professional Identity and Counsellor Education - Hiebert, Bryan; Simpson, Liz; Uhlemann, Max R. (Canadian Journal of Counselling and Psychotherapy, 1992)
The purpose of this paper is to provide a perspective on the current sense of professional identity amongst counsellors and counselling psychologists in Canada, with the hope of encouraging more attention to this issue amongst counsellors, counselling psychologists, and counsellor educators. Findings from a pilot survey on professional identity suggest that the three groups agree on the definition of counselling psychology, but there are considerable discrepancies between the perceptions and practices of all three groups. As well, there is little agreement on how counselling psychology is similar to or different from other helping professions. Conclusions and implications of these findings for the development of a more clear professional identity are discussed.